Characterizations of Loxodromes on Rotational Surfaces in Euclidean 3–Space - Aksoyak, Ferdağ Kahraman; Demirci, Burcu Bektaş; Babaarslan, Murat (Kazım İlarslan, 2023)
In this paper, we study on the characterizations of loxodromes on the rotational surfaces satisfying some special geometric properties such as having constant Gaussian curvature and a constant ratio of principal curvatures (CRPC rotational surfaces). First, we give the parametrizations of loxodromes parametrized by arc-length parameter on any rotational surfaces in E 3 and then, we calculate the curvature and the torsion of such loxodromes. Then, we give the parametrizations of loxodromes on rotational surfaces with constant Gaussian curvature. Also, we investigate the loxodromes on the CRPC rotational surfaces. Moreover, we give the parametrizations of loxodromes on the minimal rotational surface which is a special case of CRPC rotational surfaces. Finally, we give some visual examples to strengthen our main results via Wolfram Mathematica 10.4.
Keywords: Loxodrome; Curvature; Torsion; Rotational Surfaces; Gaussian Curvature; Mean Curvature; Minimal Surfaces; Helix; Asymptotic Curve; Euclidean 3-Space